Экспериментальное исследование выдавливания в условиях вихревого течения металла - Кротенко, Галина Анатольевна (НТУ "ХПИ", 2006)
The article is devoted to methods which gives possibility experimental researches of complicated processes of squeezing, verification of adequacy of mathematical model and exactness of theoretical researches
Keywords: математическая модель; деформация; трение; пуансоны; пресс; хвостовик